Notes on Mexican Art, Social Movements, and Anzaldúa's “Conocimiento” - McCaughan, Ed (Social justice, 2006)
Part of a special issue on art, power, and social change. Mexico has a long history of politically engaged art. The work of muralists such as Diego Rivera and David Siqueiros from the first half of the 20th century is familiar to many people. However, beginning in the 1960s and 1970s, visual art strategies were transformed by epistemological paradigms stemming from indigenous, ethnic, and feminist social movements and by new developments in the art world, including conceptual art and installation. Contemporary Mexican art differs in two important ways from earlier political art: the production of the art involves the artists in an interdisciplinary pursuit of knowledge drawn from a myriad of diverse fields and their own individual and cultural subjectivity; and the works engage the public in a multisensorial and potentially spiritual encounter that reilluminates the past and permits new ways of knowing. The writer discusses some examples of this new Mexican art in detail.